STRESS AND CUE-ELICITED CRAVING AND REACTIVITY IN MARIJUANA-DEPENDENT INDIVIDUALS - McRae-Clark, Aimee L. (2011)
RATIONALE: Cue-elicited craving and stress responses have been identified as predictors of relapse in drug dependence, but little research exists on the contribution of these factors to marijuana use specifically. OBJECTIVES: The aims of the present study were to evaluate (1) responses to a psychological stressor, (2) responses to marijuana-related cues, and (3) if an exposure to a psychological stressor augmented craving subsequently elicited by marijuana-related cue exposure in marijuana-dependent individuals. METHODS: Subjective (craving, stress), neuroendocrine (ACTH, cortisol), and physiologic responses to the presentation of neutral and marijuana cues were assessed after randomization to a stress (Trier Social Stress Task; TSST) or no-stress control condition in marijuana-dependent individuals. Outcome measures were assessed at baseline, post-stressor/pre-neutral cue, post-neutral cue, and post marijuana cue. RESULTS: 87 participants completed procedures (stress group, n=45; non-stress group, n=42). The stress group had a significant increase over the non-stressed group in stress rating (p<0.001), craving (p=0.028), cortisol (p<0.001), and ACTH (p<0.001) after completion of the TSST. An increased craving response for all participants was seen following presentation of the marijuana cues (p=0.005). Following the TSST or no-stress condition, the non-stressed group had an increase in craving to marijuana cues as compared to neutral cues (p=0.002); an increase in craving was not observed in the stress group (p=0.404). CONCLUSIONS: Marijuana cue exposure and a social stressor increased craving in marijuana-dependent individuals. Completion of the TSST did not increase craving response to subsequent marijuana-cue exposure.